Pengembangan Dark Tourism Sebagai Salah Satu Daya Tarik Wisata Tana Toraja - Andi Nabila Aura Maharani; Agung Sulistyo; Dwi Agus Kristianto; Edy Suharyono; Ertanta Ari Sudanang (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
Indonesia has the potential for beauty and rich resources that are recognised worldwide. This diversity can be developed through the tourism sector. Tourism development can be done with the right strategies. As a development effort, attractiveness instruments are important to pay attention to. This research was conducted to develop the potential of the Lo'Ko Mata tourist attraction so that it is sustainable and provides broad benefits. This step can be done through an analysis of the internal and external environment. A mixed-methods design was used in this research, along with SWOT-8K analysis, to reveal various aspects of development. The Informant for this research is the manager of the public relations division. Based on data analysis, the Lo'Ko Mata tourist attraction is in Quadrant 1-A. These results can be used as a basis for managers to implement aggressive growth strategies. As an effort to create sustainable tourism, managers can maximise the various strengths they have, such as: 1) uniqueness of tourist attractions; 2) tourism promotion; 3) maintenance of tourist attractions; 4) role of the community; 5) potential of tourist attractions; 6) economic conditions of the community; 7) technological development; 8) tourism development; 9) cleanliness of tourist attractions; and 10). operational permit. Apart from maximising existing potential, managers can also take advantage of various opportunities that arise, including: 1) collaboration with external parties; 2) HR skills; and 3) HR welfare. Furthermore, through instruments of weakness and threat, managers need to design strategies to minimise and eliminate negative impacts. Formulating the right strategy will have an impact on management sustainability.